Phosphate intake, hyperphosphatemia, and kidney function - Rubio-Aliaga, Isabel; Krapf, Reto (Pflügers Archiv, 2022)
Phosphate is essential in living organisms and its blood levels are regulated by a complex network involving the kidneys, intestine, parathyroid glands, and the skeleton. The crosstalk between these organs is executed primarily by three hormones, calcitriol, parathyroid hormone, and fibroblast growth factor 23. Largely due to a higher intake of ultraprocessed foods, dietary phosphate intake has increased in the last decades. The average intake is now about twice the recommended dietary allowance. Studies investigating the side effect of chronic high dietary phosphate intake suffer from incomplete dietary phosphate assessment and, therefore, often make data interpretation difficult. Renal excretion is quickly adapted to acute and chronic phosphate intake. However, at the high ends of dietary intake, renal adaptation, even in pre-existing normal kidney function, apparently is not perfect. Experimental intervention studies suggest that chronic excess of dietary phosphate can result in sustained higher blood phosphate leading to hyperphosphatemia. Evidence exists that the price of the homeostatic response (phosphaturia in response to phosphate loading/hyperphosphatemia) is an increased risk for declining kidney function, partly due by intraluminal/tubular calcium phosphate particles that provoke renal inflammation. High dietary phosphate intake and hyperphosphatemia are progression factors for declining kidney function and are associated with higher cardiovascular disease and mortality risk. This is best established for pre-existing chronic kidney disease, but epidemiological and experimental data strongly suggest that this holds true for subjects with normal renal function as well. Here, we review the latest advances in phosphate intake and kidney function decline.